A novel class of nickel(ii) complexes containing selenium-based bidentate ligands applied in ethylene oligomerization. Issue 106 (1st November 2016) - Dresch, Lucielle C.; de Araújo, Bruno B.; Casagrande, Osvaldo de L.; Stieler, Rafael
Abstract : A series of nickel(ii ) complexes [NiBr2 (N^Se)2 ] (Ni1–Ni5 ) based on bidentate N^Se ligands were prepared by reacting arylselenyl–pyrazolyl ligands (L1–L5 ) with NiBr2 (DME) (DME = 1, 2-dimethoxyethane). Abstract : A series of nickel(ii ) complexes [NiBr2 (N^Se)2 ] (Ni1–Ni5 ) based on bidentate N^Se ligands were prepared by reacting arylselenyl–pyrazolyl ligands (L1–L5 ) with NiBr2 (DME) (DME = 1, 2-dimethoxyethane). All Ni complexes were characterized by IR spectroscopy, elemental analysis, high-resolution mass spectrometry (HRMS), and by X-ray crystallography for Ni4 . X-ray crystallographic analyses of Ni4 revealed an octahedral environment for the nickel atom and the presence of selenium–nickel bonds. Upon activation with methylaluminoxane (MAO), all Ni complexes showed moderate to good activities in ethylene oligomerization [TOF = 6.2–23.0 × 10 3 (mol ethylene) per (mol Ni) per h], producing mostly α-C4 (87.2–94.1 wt%) as the main product. The ligand environment, i.e. the substituents on the pyrazolyl and arylselenyl units, as well as the reaction parameters, influence the catalytic activity and selectivity towards the production of 1-butene. Under optimized reaction conditions (toluene, 400 equiv. of MAO, 40 °C and 20 min), the Ni2 /MAO catalytic system yielded TOF values up to 109.2 × 10 3 (mol ethylene) per (mol Ni) per h with good selectivities for α-C4 (85.4 wt%).